Women's Struggle For Participation In Public-PolicymakingProcesses In Anchee Min's Empress Orchid (2004) And The Last Empress (2007): A Feminist Criticism - Rimbawati, Linggar, Dr. M. Thoyibi, M.S, Titis Setyabudi, S.S. M. Hum (2014)
The major problem of this study is how the struggle of women in process of public-policymaking is reflected in novels of Empress Orchid (2004) and The Last Empress (2007) written by Anchee Min based on the feminist criticism. The objective of the study is to analyze the novels based on the structural elements and the feminist analysis. In analyzing Empress Orchid (2004) and The Last Empress (2007), the researcher uses the qualitative method and feminist approach. The data sources consist of primary data and secondary data. The primary data are novels of Empress Orchid (2004) and The Last Empress (2007) and the secondary data are books and literatures related to the analysis such as books of feminist issue, literary theory, the author's biography, the journals of USA, and other relevant information to analysis of this research paper. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions; first, from the structural elements of the novel it is shown that Anchee Min wants to uncover her idea about how women experience the inequality in all aspects of life, included political life. Second, based on the feminist criticism, Empress Orchid (2004) and The Last Empress (2007) show that there is a correlation between the social realities of American society in the twenty-first century.